Exploring Ibn Khaldun’s thoughts on the ethical issues from social networking sites - Mohamed Najid, Mohamad Hafizuddin; Zulkifli, Zahidah; Othman, Roslina; Rokis, Rohaiza (IEEE, 2018)
Social Networking Sites (SNS) is a popular platform for sharing and communicating with people all around the world. Its popularity brings in various communication contents discussed by the public. However, SNS is an open communicative channel which has no specific rules for its users to follow. This result in its misappropriation by some people to share their unethical values or destructive ideas with others. This paper is in the view that computer ethics must follow Islamic ethics. Thus the aim of this paper is to identify the ethical issues in SNS with reference to Ibn Khaldun’s thoughts through his masterpiece The Muqaddimah. It has undertaken a qualitative methodology approach through a textual analysis method. The study has focused on acquiring expert verification throughout a proposed list of Ibn Khaldun’s thoughts. The findings show ten (10) Ibn Khaldun’s thoughts which have been justified as a reference to ethical issues in SNS nowadays. In conclusion, Ibn Khaldun’s thoughts may have contributed to ethical issues in SNS. These findings may guide other researchers to further deliberate the contributions of Ibn Khaldun in the disciplines of human social networking and information computer technology.